Novel concept of fine-tuned QFT control applied to a robot manipulator - Saddique, S.M.; Moghavvemi, M.; Tamjis, M.R. (ACTA Press, 1998)
This paper deals with the problems of robot control and the hardware required for study of various control algorithms on a four-degree-of-freedom laboratory-type robot. The authors investigate combining a classical high-gain controller based on quantitative feedback control theory (QFT) with an adaptive control strategy. The new technique, named "fine-tuned QFT control scheme," is applied to control a four-degree-of-freedom robot arm for trajectory tracking. The entire control scheme was implemented on an IBM-compatible personal computer to drive a four-axis robot in real time. The main results of the experiments and the hardware and software issues are presented, and some comparative studies are made.